La rabbia del fiume e la violenza degli argini: Appunti su un post-alluvione per una “etnografia civica” nei disastri - Petrangeli, Enrico (Antropologia Pubblica, 2024)
The article explores the aftermath of the flooding of the river Paglia, the biggest among the Tiber tributaries, in the area of Orvieto on November 12, 2012. It highlights the activities of the Val di Paglia bene comune association (Paglia Valley Common Resource) (VPbc). VPbc has progressively become an agent of research and action that rose out of the cultural shock caused by the flood. The association aims at identifying positive outcomes of new social functions and community development. The article begins by a critical reading of the official description of the disaster, highlighting the limits of naturalistic reductionism. It proposes arguments for a deeper study on the social drama experienced by the Orvieto community. It continues by presenting the structure of the VPbc, its aims, strategies and social structure. The author, currently president of the VPbc, provides a reflexive analysis related to his position as a member of the community and observer/participant linked to the “transformative knowledge” paradigm. The final chapters suggest that the VPbc’s activities represent an ethnographic terrain and proposes the term “civic ethnography” for defining the active mediation work aimed at matching local knowledge and technical skills. Finally, technical-bureaucratic power practices are mapped as a preparatory step towards the dialectic between communities and institutions.